Crystallization Atmosphere and Substrate Effects on the Phase and Texture of Chemical Solution Deposited Strontium Niobate Thin Films. Issue 3 (12th February 2013) - Campion, Michael J.; Brown‐Shaklee, Harlan J.; Rodriguez, Mark A.; Richardson, Jacob J.; Clem, Paul G.; Ihlefeld, Jon F.; Trolier‐McKinstry, S.
<x xml:space="preserve">Abstract</x> Strontium niobate (Sr:Nb = 1:1) thin films were prepared via chemical solution deposition on (001)‐oriented SrTiO3, (001)p‐oriented LaAlO3, (0001)‐oriented sapphire, and polycrystalline alumina substrates. Crystallization in oxygen at 1000°C yielded Sr2Nb2O7 films on all substrates with strong (010) orientation. Films on LaAlO3 and SrTiO3 single‐crystal substrates possessed a small amount of preferred in‐plane orientation, whereas films prepared on sapphire and polycrystalline alumina substrates were fiber textured. Films crystallized at 900°C in a low oxygen atmosphere ( 10−21 atm pO2) formed a randomly oriented polycrystalline perovskite, SrNbO3−δ on all substrates. A similar set of films crystallized at 900°C at a slightly higher oxygen partial pressure ( 10−15 atm pO2) was comprised of Sr2Nb2O7 and SrNbO3−δ phases, exposing the dependence of phase formation on oxygen partial pressure. When subjected to a high‐temperature anneal in oxygen, the SrNbO3−δ phase is shown to transform into Sr2Nb2O7, however, Sr2Nb2O7 did not significantly reverse transform into SrNbO3−δ after annealing in low oxygen partial pressure atmospheres.